Study of Dye-Sensitized Solar Cells by Scanning Electron Micrograph Observation and Thickness Optimization of Porous TiO2 Electrodes - Seigo Ito; Mohammad K. Nazeeruddin; Shaik M. Zakeeruddin; Peter Péchy; Pascal Comte; Michael Grätzel; Takaki Mizuno; Atsushi Tanaka; Tsuguo Koyanagi (International Journal of Photoenergy)
In order to improve the photoenergy conversion efficiency of dye-sensitized solar cells (DSCs), it is important to optimize their porous TiO2 electrodes. This paper examines the surface and cross-sectional views of the electrodes using scanning electron micrography. Two types of samples for cross-sectional viewing were prepared by mechanically breaking the substrate and by using an Ar-ion etching beam. The former displays the surface of the TiO2 particles and the latter shows the cross-section of the TiO2 particles. We found interesting surface and cross-sectional structures in the scattering layer containing the 400 nm diameter particles, which have an angular and horned shape. The influence of TiO2 particle size and the thickness of the nanocrystalline-TiO2 electrode in DSCs using four kinds of sensitizing dyes (D149, K19, N719 and Z907) and two kinds of electrolytes (acetonitrile-based and ionic-liquid electrolytes) are discussed in regards to conversion efficiency, which this paper aims to optimize.